Influence of sintering temperature on structure, physical, and optical properties of wollastonite based glass-ceramic derived from waste eggshells and waste soda-lime-silica glasses - Chen, Hongxu; Azis, Raba'ah Syahidah; Mohd Zaid, Mohd Hafiz; Amin Matori, Khamirul; Ismail, Ismayadi (International Institute for the Science of Sintering, 2024)
Calcium oxide from discarded eggshells and waste soda-lime-silica were utilized in this study to make wollastonite (CaSiO3) based glass-ceramics. The calcium oxide and silica were made using the melt-quenching process and sintered for 2 hours at 700 to 1000 °C. The XRD data verified that the wollastonite crystalline peak appeared at high sintering temperatures, with crystalline phase values of 39.74%, 47.37%, and 48.91% as the sintering temperature increased at 800-1000°C, respectively. Additionally, crystalline size and phase have no obvious change at 800-1000°C, where the intensity has increased by the sintering temperature. The FTIR spectra revealed the wollastonite phase vibration at the wavelength of 501, 650, 715, 808, 931, and 2129 cm-1. Additionally, the FTIR spectral confirm the Si-O-Ca vibration band at the wavelength of 650 cm-1. For the optical sample, the value of indirect allowed transition with n=2 is the ideal value of the optical band gap based on a band gap rise from 3.89 to 4.23 eV with increasing sintering temperature. The value n=2 which is the indirect allowed transition is the optimal value of the optical band gap based on the value increase from 3.89-4.23 eV as the temperature increase. The synthesis approach introduced the low-cost method, recycle approach, simple and yet uses cheap starting materials for fabrication of wollastonite glass-ceramics product. Keywords: Waste glass; Melt quenching; Density; XRD; UV-Vis.